Notary's Authority in Providing Legal Counseling to the Public Regarding Notarial Deeds - Nurjanah; Muhibbin; Sunardi (Journal of Law, Politic and Humanities, 2025)
Notaries in providing legal counseling are based on Article 15 paragraph 2 letter e of the UUJN, namely providing legal counseling in connection with the making of deeds. It is very important to improve legal understanding related to the making of notarial deeds. Notaries have an obligation to convey information clearly and provide appropriate advice to clients, while maintaining professionalism and following the applicable code of ethics. Thus, effective legal counseling by notaries can help ensure the protection of individual rights and legal certainty in society. The obstacles to legal counseling include the low level of basic education of the community, lack of legal knowledge among the community, and distrust of the legal process. The community often has difficulty understanding the legal terminology and procedures required for making notarial deeds, and does not understand the importance of notarial deeds in protecting their rights and providing legal certainty. To overcome these obstacles, several strategies can be taken. Strategies to improve legal understanding through counseling by notaries in villages, as well as improving clear and effective communication, are important steps to clarify complex legal concepts for the community.